Scale validation to evaluate WhatsApp dependence (WADS) - King,Anna Lucia Spear (2019)
ABSTRACT BACKGROUND INFORMATION: One of the most popular social networks is WhatsApp. Abusive use of this tool has produced significant changes in behavioral and social behaviors and habits of individuals. Therefore, research is needed to allow us to specifically evaluate the interaction of WhatsApp with the daily lives of individuals. OBJECTIVE: Production and validation of a scale to evaluate WhatsApp dependence (WADS). METHODS: Validation performed in 5 phases: 1- initial scale construction with 20 questions, 2- expert evaluation, 3- application in volunteers, 4- statistical analysis and results, and 5- elaboration of the final version of the validated WADS. RESULTS: We obtained a descriptive statistical analysis, a clear-cut separation of dependents vs. non-dependents and a successful factorial analysis. These results provided a validated version of WADS. CONCLUSIONS: We were able to construct a final version of WADS adequate to clinical contexts and to be used in future research to evaluate dependence of this digital tool. WADS will contribute to the conscious use of WhatsApp, hopefully reducing harmful effects and improving quality of life.